The Impact of Social Support, Intimate Partner Violence, and Pregnancy Plans on Antenatal Depression: A Meta-Analysis Study - Putri, Dominika Risnanda Alfinsia; Pamungkasari, Eti Poncorini; Adriani, Rita Benya (Journal of Maternal and Child Health, 2024)
Background: Antenatal depression is a type of depression that occurs during pregnancy and affects about 20% of pregnant women. This study aims to analyse the effects and estimate the magnitude of the effects of social support, intimate partner violence and pregnancy status on the incidence of antenatal depression with a meta-analysis. Subject and Method: The meta-analysis was performed using a PRISMA flowchart and a PICO model. Population: pregnant women. Intervention: strong social support, experiencing violence by intimate partners, and planned pregnancy status. Comparison: weak social support, no violence by intimate partners, and unplanned pregnancy status. Outcome: antenatal depression. The online databases used are Google Scholar, Hindawi, PubMed, Science Direct, Scopus, and ResearchGate. There were 17 cross-sectional studies published in 2018-2023 that met the inclusion criteria. Analysis was done with RevMan 5.3. Results: Meta-analysis was conducted on 17 cross-sectional studies from Australia, Thailand, Nepal, Bangladesh, Nigeria, Ethiopia, Rwanda, Norway, and Jamaica. Sample size = 11,517 study subjects. The risk of antenatal depression increases with intimate partner violence (aOR= 2.13; CI 95%= 1.65 to 2.74; p<0.001). The risk of antenatal depression decreased with strong societal support (aOR= 0.47; CI 95%= 0.38 to 0.58; p<0.001) and planned pregnancy (aOR= 0.45; CI 95%= 0.24 to 0.84; p=0.01). Conclusions: The risk of antenatal depression increases when there is intimate partner violence, decreases if social support is obtained and pregnancy is planned.